Role of nucleation of bile liquid crystal in gallstone formation - Yang, Hai-Ming (World J Gastroenterol, 2003)
AIM: To explore the role of bile liquid crystal in the process of gallbladder stone formation and to provide bases for preventing and treating cholelithiasis. METHODS: 46 guinea pigs, half males and half females, were randomly divided into control group and stone-causing group. Normal feed and stoneleading feed were used respectively to raise guinea pigs in the control group and stone-causing group. The guinea pigs were killed in three batches during the raising period. Under polarizing microscope, the pattern changes of bile liquid crystal in the gallbladder biles of the guinea pigs in the control group and stone-causing group were dynamicly observed respectively in single-blind trial. RESULTS: It was found that there were few crystals in the guinea pigs’ biles of the control group, and their Malta cross was small and scattered, and existed in single form. With the increase of the feeding days, bile liquid crystals grew and Malta cross became bigger with their distribution densified, denser somewhere, but always existed in single form. While those of the stone-causing group had more bile liquid crystals, Malta cross was big and merged in strings. With the increase of the feeding days, bile liquid crystals grew in amount and strings of Malta cross increased and became bigger. The crosses in strings were arranged more and more regularly and they gradually changed into stone crystals. CONCLUSION: Formation of gallbladder stone is a process of nucleation from different substances, and the causing-stone gallbladder bile is a constantly supersaturated solution, and bile liquid crystal is a nucleation factor in the formation of gallbladder stones. The process of nucleation includes gathering, merging and phase-changing of bile liquid crystals. The process of gathering, merging of bile liquid crystal is the key to nucleation.